Plant genotype, microbial recruitment and nutritional security - Patel, Jai S.; Singh, Akanksha; Singh, Harikesh B.; Sarma, Birinchi K. (Frontiers in Plant Science, 2015)
Agricultural food products with high nutritive value are always preferred over food products with low nutritive value. Efforts are being made to increase the nutritive value of food by incorporating dietary supplements to the food products. The same is more desirous if the nutritive value of food is increased under natural conditions in the food products especially in the agricultural produces. Fragmented researches have led to the conclusion that it is possible to increase nutritive value of the agricultural products naturally in agricultural fields. The rhizosphere is of vital importance in this regard for not only health and nutritional status of plants but also for the microorganisms colonising the rhizosphere. Remarkably robust composition of plant microbiome with respect to other soil environments clearly suggests the role of plant host in discriminating its colonisers. A large amount of biotic and abiotic factors are believed to manipulate the microbial communities in the rhizosphere. However, plant genotype has proven to be the key in giving the final shape of the rhizosphere microbiome.